A theory of social thermoregulation in human primates - IJzerman, Hans; Coan, James A.; Wagemans, Fieke M. A.; Missler, Marjolein A.; Beest, Ilja van; Lindenberg, Siegwart; Tops, Mattie (Frontiers in Psychology, 2015)
Beyond breathing, the regulation of body temperature—thermoregulation—is one of the most pressing concerns for many animals. A dysregulated body temperature has dire consequences for survival and development. Despite the high frequency of social thermoregulation occurring across many species, little is known about the role of social thermoregulation in human (social) psychological functioning. We outline a theory of social thermoregulation and reconsider earlier research on people’s expectations of their social world (i.e., attachment) and their prediction of the social world. We provide support and outline a research agenda that includes consequences for individual variation in self-regulatory strategies and capabilities. In our paper, we discuss physiological, neural, and social processes surrounding thermoregulation. Emphasizing social thermoregulation in particular, we appeal to the economy of action principle and the hierarchical organization of human thermoregulatory systems. We close with future directions of a crucial aspect of human functioning: The social regulation of body temperature.